(untitled) (Indonesian Sports Justice Review, 2024)
Racial and ethnic inequality remains a persistent issue in Indonesia’s sports sector, where certain communities continue to face systemic barriers in accessing sports opportunities and achieving success in elite competitions. This paper investigates the role of racial and ethnic inequality in Indonesian sports, focusing on the representation of marginalized ethnic groups in high-performance sports and the structural barriers to their participation. The research employs a mixed-methods approach, incorporating demographic analysis, interviews with athletes from underrepresented ethnic backgrounds, and an examination of sports policies and funding allocation. The paper critically assesses how stereotypes, lack of access to quality training facilities, and limited cultural acceptance affect athletes from minority groups. The study concludes by offering policy recommendations to promote fair representation, including targeted support for ethnic minorities, anti-discrimination measures, and the role of the media in fostering inclusivity.